Career Search Efficacy pada Generasi Z - Ellen Theresia; Indah Puspitasari; Marissa Chitra Sulastra; Tery Setiawan (Universitas Kristen Maranatha, 2025)
Generation Z, as the youngest generation in the workplace, has greater access to technology and information, including career exploration. We assume, that family remains an important role in determining career search efficacy. The purpose of this study is to determine the relationship between career related parental support and career search efficacy in Generation Z. The respondents in this study are Generation Z, aged 18-27 years old (N=160). Based on confirmatory factor analysis in this study, career search efficacy is more fit to be formed by a three-factor scale, rather than a four-factor scale. Furthermore, hierarchical regression analysis showed, the instrumental assistance dimension of career related parental support was negatively related to career search efficacy, while emotional support was found to be positively related to career search efficacy. Our findings provided insights into the different roles of career-related parental support dimensions on career search efficacy among Generation Z.